Seed layer effect on the (0 0 2) texture and piezoelectric properties of pulsed-DC sputtered AlN thin films. Issue 1 (2nd January 2016) - Hasheminiasari, M.; Lin, J.
Abstract: Piezoelectric aluminium nitride (AlN) thin films were deposited by reactive sputtering of Al metal target in nitrogen atmosphere using a pulsed closed field unbalanced magnetron sputtering system on various substrates using different underlayers (seed layer) such as Pt and Mo. The texture, orientation and piezoelectric properties of AlN films were characterised by means of X-ray diffraction, field emission scanning electron microscopy and laser interferometry. A Michelson laser interferometer was designed to obtain the converse piezoelectric response of the deposited AlN thin films. It was found that the incorporation of different seed layers at various working pressure in the sandwiched structure, significantly affected the (0 0 2) orientation and the piezoelectric response of AlN thin films.